Production and composting of waste-filled biofilms as a sustainability educational experience for a secondary school setting - Vicentini, Greta; Mattiello, Sara; Santulli, Carlo (Education and Development Research, 2025)
Waste upcycling is often seen as a scattered concept, difficult to be put into practice in an educational yet scientific context. The idea is to provide an educational experience able to supply the students a wider perspective over how waste can be brought back into the productive system, until at all possible not. Outsourcing and characterization of waste, production of biofilms, home composting experiments. The experimentation gives a practical view of what is meant by circular economy moreover suggesting ideas about possible options for selecting waste and starting characterising it. In particular, it offers indications about the scientific method for testing materials including waste and being aware of their end-of-life, which all have influence on sustainability of the process. Ideally, depending on the time allotted for experiments, the work can be repeated iteratively to improve the results. Also, a database about possible local waste for DIY production of bioplastics can be generated over time, including considerations about ease of outsourcing, availability, seasonality, etc.